KERAGAAN MORFOLOGI DAN HASIL VARIETAS UNGGUL BARU PADI DENGAN PENGELOLAAN TANAMAN TERPADU DILAHAN SAWAH TADAH HUJAN KABUPATEN JEPARA - Budi Winarto; Sodiq Jauhari (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2019)
Morphology Performances and Yield of New Superior Rice Variety with Integrated Crop Management in Rainfedland Jepara District. One constraint for increasing rice production in rainfedland Jepara District is the availability of adaptive improved rice varieties with high yield. The purpose of this assessment are: (1) to analyze the morphological performance and yield potential of some new superior varieties in rainfedland Jepara District (2) to assess the level of main rice pest and diseases attack and the presence of natural pest’s enemies, and (3) to assess the responses and perceptions of farmers towards integrated crop management applications in rice production. The assessment was conducted in ranfedland Mayong Kidul Village, Mayong Sub-district, Jepara District by involving Lestari Farmer’s Group on the second planting season of 2015. The assessment also employed A Randomized Block Design with three replications and rice variety as treament: Inpari-30, Inpari-31, Inpari-10, Conde, mekongga and varietas Ciherang as the control variety.  The collected data of morphology and rice yield were analyzed using analysis of variance,  then the mean difference values between treatments was further tested using the least significant difference test at p = 0.05. The results showed that there were influences of rice varieties on plant height, number of tillers, pests and diseaces as well as yield and yield component of the five rice varieties. The Mekongga variety is the most suitable rice variety that could be used in rainfedland in order to improve rice productivity in rainfedland of Jepara District. This variety could produce dry rice grain up to 6.8 tons/ha, with 105.5 cm plant height, 14.1 productive tillers, 23.7 cm panicle length 566 and 176 number of filled and empty grains 5 panicles respectively, 4.5 pest and diceases attack level, and is able to increase grain yield up to 30.7% compared to that of control variety. Respondent farmers have a positive perception to the concept of integrated crop management with a value of 68.3%. The implication of these results is that the utilization of new superior rice varieties especially Mekongga have a high potential for improving rice productivity in rainfedland of Jepara District.  Keywords: New Superior Rice Varieties, rainfedland, ICM, Jepara ABSTRAK Keragaan Morfologi dan Hasil Varietas Unggul Baru Padi dengan Pengelolaan Tanaman Terpadu di Kabupaten Jepara.  Salah satu kendala peningkatan produktivitas padi di lahan sawah tadah hujan Kabupaten Jepara adalah ketersediaan varietas unggul yang adaptif dengan produktivitas tinggi. Tujuan pengkajian ini adalah (1) mengkaji keragaan morfologi dan potensi hasil beberapa VUB padi di lahan sawah tadah hujan (2) mengkaji tingkat serangan hama dan penyakit utama padi serta keberadaan musuh alami hama, dan (3) mengkaji respon dan persepsi petani terhadap penerapan PTT padi. Pengkajian dilakukan di lahan sawah tadah hujan Desa Mayong Kidul Kecamatan Mayong Kabupaten Jepara, Kelompok Tani Lestari pada musim tanam ke-2 tahun 2015. Pengkajian ini menggunakan Rancangan Acak Kelompok dengan tiga ulangan dan sebagai perlakuan adalah varietas padi: Inpari-30, Inpari-31, Inpari-10, Conde dan mekongga serta varietas Ciherang sebagai pembanding. Data yang terkumpul dianalisis menggunakan analisis varian (anova), selanjutnya perbedaan nilai tengah antar perlakuan diuji lanjut menggunakan uji beda nyata terkecil (BNT) pada p=0.05. Hasil pengkajian menunjukkan bahwa terdapat pengaruh nyata varietas padi terhadap tinggi tanaman, jumlah anakan, perkembangan OPT, hasil dan komponen hasil gabah dari kelima varietas tanaman padi yang diuji. Varietas Mekongga merupakan VUB padi yang paling sesuai ditanam di lokasi pengkajian dalam rangka meningkatkan produktivitas padi. Varietas ini menghasilkan gabah kering giling hingga 6.8 ton/ha, tinggi tanaman 105.5 cm, jumlah anakan produktif 14.1, panjang malai  23.7 cm, jumlah gabah bernas 566 butir  per 5 malai, jumlah gabah hampa 176 gabah hampa per 5 malai dan tingkat serangan OPT 4,5%, serta  mampu meningkatkan hasil gabah hingga 30.7% dibanding kontrol. Petani juga memiliki persepsi positif terhadap konsep PTT dengan nilai mencapai 68.3%. Implikasi hasil kajian ini adalah pemanfaatan VUB padi terutama Mekongga memiliki potensi tinggi dalam meningkatkan produktivitas padi di lahan sawah tadah hujan Kabupaten Jepara. Kata kunci: VUB padi, tadah hujan, PTT, Jepara